Pouring a Little Psychological Cold Water on Online Dispute Resolution - Sternlight, Jean R (2020)
This Article examines the strengths and weaknesses of ODR (online dispute resolution) from a psychological perspective. It makes five main points:(1) The phrase ODR is too broad to be useful. This phrase encompasses many different kinds of technology (computer, phone, video, mechanical pencil), many different kinds of dispute resolution (litigation, negotiation, arbitration, mediation), disputes arising in many different contexts (consumer, family, property, tax, employment, etc.), and many different roles (technology as neutral, technology as aide to neutral, technology as aide to disputant, etc.). In order to consider whether and when ODR can be most useful we will need to tease apart these various types of ODR.(2) Those who design all types of ODR should pay substantial attention to the psychology underlying disputes, and be conscious that merely using ODR to foster rational exchanges of information will likely not yield ideal dispute resolution. Many empirical studies already show that human psychology is critically important to dispute resolution.(3) In the short term my instinct is that humans will often have a comparative advantage over computers or other technology in handling the psychological aspects of disputes. I believe humans are likely to be more adept than technology at creating empathy, building rapport and trust, and helping to persuade people to rethink their strongly felt beliefs.(4) At the same time, we should all appreciate that technology is evolving quickly, and potentially will be able to do things we can’t easily imagine. As ODR designers work to refine ODR approaches they should focus on the human and psychological side of disputes. Perhaps holographic mediators will actually be able to build better empathy and rapport than many humans?(5) Rather than trust our instincts regarding the comparative superiority of humans and technology to handle human psychology we should test these approaches empirically. I appreciate that even my own instincts on these fronts may be wrong